Explanations : styles of explanation in science - Cornwell, John, 1940- (Oxford University Press, 2004)
Our lives, states of health, relationships, behaviour, experiences of the natural world, and the technologies that shape our contemporary existence are subject to a superfluity of competing, multi-faceted and sometimes incompatible explanations. Widespread confusion about the nature of 'explanation' and its scope and limits pervades popular exposition of the natural sciences, popular history and philosophy of science. This fascinating and intriguing book explores the wayexplanations work, why they vary between disciplines, periods, and cultures, and whether they have any necessary boundaries.